Comprehensive care programme for patients with chronic obstructive pulmonary disease: a randomised controlled trial. Issue 2 (28th July 2016) - Ko, Fanny W S; Cheung, N K; Rainer, Timothy H; Lum, Christopher; Wong, Ivor; Hui, David S C
Abstract : Background: There have been no randomised controlled trials that specifically evaluate the effect of a comprehensive programme with multidisciplinary input on patients who have just been discharged from hospital after treatment of acute exacerbation of COPD (AECOPD). The aim of this study was to assess whether a comprehensive care programme would decrease hospital readmissions and length of hospital stay (LOS) for patients with COPD. Methods: Patients discharged from hospital after an episode of AECOPD were randomised to an intervention group (IG) or usual care group (UG). The IG received a comprehensive, individualised care plan which included education from a respiratory nurse, physiotherapist support for pulmonary rehabilitation, 3-monthly telephone calls by a respiratory nurse over 1 year, and follow-up at a respiratory clinic with a respiratory specialist once every 3 months for 1 year. The UG were managed according to standard practice. The primary outcome was hospital readmission rate at 12 months. Results: 180 patients were recruited (IG, N=90; UG, N=90; mean±SD age 74.7±8.2 years, 172 (95.6%) men; mean±SD FEV1 45.4±16.6% predicted). At 12 months, the adjusted relative risk of readmission was 0.668 (95% CI 0.449 to 0.995, p=0.047) for the IG compared with the UG. At 12 months, the IG had a shorter LOS (4.59±7.16 vs 8.86±10.24 days, p≤0.001), greater improvement in mean Modified Medical Research Council Dyspnoea Scale (−0.1±0.6 vs 0.2±0.6, p=0.003) and St George's Respiratory Questionnaire score (−6.9±15.3 vs −0.1±13.8, p=0.003) compared with the UG. Conclusions: A comprehensive COPD programme can reduce hospital readmissions for COPD and LOS, in addition to improving symptoms and quality of life of the patients. Trial registration number: NCT 01108835, Results.